(untitled) (EuroMediterranean Biomedical Journal, 2026)
Intra-abdominal desmoplastic small round cell tumors are rare aggressive neoplasms, with a very poor prognosis, observed in young adults with a male predominance. Their etiology is unknown and the diagnosis is based on histopathology, immunohistochemistry and cytogenetics. Histological analysis shows typically clusters of round cells separated by abundant desmoplastic stroma. These tumors exhibit a multi-marker immunohistochemistry profile expressing the three embryonic lineages: epithelial, neural and mesenchymal. They are positive for desmin and cytokeratin and are characterized by a specific recurring translocation t (11: 22) (q12 - p13), which involves EWSR1 WT1 gene. They are usually fatal despite an aggressive multidisciplinary therapeutic approach. Hereby we report the case of a 39 year old man who presented with an intra-abdominal desmoplastic small round cell tumor. The diagnosis was made by radiological, histological and immunohistochemistry profile analyses of a CT scanguided biopsy. This article also includes a mini review of the literature.